Synthesis and characterization of carbazole-based conjugated polymer via direct arylation polymerization - Wong, Xin Lin (2020)
Conjugated polymers, with excellent optical and electrical properties, have appeared as promising operative materials for a diverse range of applications. Donor-Acceptor (D-A) framework, which copolymerizes electron-donors and electron- acceptors alternatively in conjugated backbones, has proven to be the most effective strategy for obtaining low bandgap polymers that desirable for optoelectronic applications. The synthesis of conjugated polymers is primarily relied on conventional cross-couplings, in particularly, Suzuki and Stille couplings, which involve the use of costly toxic organometallic reagents for monomers’ functionalization. Despite robust and effective, these protocols produce stoichiometric quantities of toxic byproducts. Direct arylation polymerization (DArP) is a newly established synthetic strategy that provides a clean and low cost pathway towards conjugated polymers. It allows direct coupling of aryl halides and aromatic compounds without preactivation of Carbon-Hydrogen (C-H) bonds. In this research, an alternating D-A type copolymer based on N-9-hexadecyl-2,7-dibromocarbazole and 4,7-di(2-thienyl)benzothiadiazole was synthesized by DArP. This structure is modified from the classical low bandgap copolymer poly[N-9’-heptadecanyl-2,7-carbazole-alt -5,5-(4’,7’-di-2-thienyl-2’,1’,3’-benzothiadiazole)] (PCDTBT) which exhibited excellent devices performance. One-pot DArP reaction was carried out under phosphine-free condition with palladium (II) acetate as the catalyst, pivalic acid as the additive, and potassium carbonates as the base. The resulting copolymer, poly[(9-hexadecyl-2,7-carabzole-alt-4,7-di(2-thienyl)-2,1,3-benzothiadiazole)] (P1) was obtained in 44%. It showed good solubility in organic solvents and has been satisfactorily characterized by FTIR and NMR. UV-Vis absorption spectra show the presence of inter-chain interaction and aggregation in the solid state. The optical bandgap of the copolymer was found to be in between 1.77 – 1.81 eV, which is slightly lower than that of the PCDTBT (1.88 eV).